2012
DOI: 10.1177/0310057x1204000116
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Practices in a Tertiary Intensive Care Unit in Saudi Arabia

Abstract: Our aim was to evaluate end-of-life practices in a tertiary intensive care unit in Saudi Arabia. A prospective observational study was conducted in the medical-surgical intensive care unit of a teaching hospital in Riyadh, Saudi Arabia. Over the course of the one-year study period, 176 patients died and 77% of these deaths were preceded by end-of-life decisions. Of these, 66% made do-not-resuscitate decisions, 30% decided to withhold life support and 4% withdrew life support. These decisions were made after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…With globalization and as the number of Western-trained physicians increase, a change in how end-of-life-discussion is handled in this part of the world is to be expected. In fact, this has already been reported by some of the most recent publications [20]. …”
Section: Discussionsupporting
confidence: 74%
“…With globalization and as the number of Western-trained physicians increase, a change in how end-of-life-discussion is handled in this part of the world is to be expected. In fact, this has already been reported by some of the most recent publications [20]. …”
Section: Discussionsupporting
confidence: 74%
“…This has been attributed to the fact that nursing staff are largely expatriate and do not speak Arabic. 9 It has also been reported that medical decisions are largely the responsibility of physicians in ICUs and therefore, nurses are not involved in this process. [14][15][16] In contrast, research conducted in Western countries has reported that nurses are now more actively and directly involved in decision-making with families and physicians 12,13 resulting in family members being more satisfied and accepting of the decisions made.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this study is addressing the real and common ethical issues faced in daily practice by physicians. Although these challenges have been addressed in the literature as isolated ethical issues in healthcare, no attempt has ever been made to collate and prioritize them in our community [10][11][12][15][16][17][18][19][20][21][22][23][24]. This study encompasses a different spectrum of physicians regarding gender, different subspecialties, training level, and whether they practiced in private or government hospitals.…”
Section: Discussionmentioning
confidence: 99%